Isolation and Characterization of a Novel Phage for Controlling Multidrug-Resistant Klebsiella pneumoniae - Qin Peng; Meng Fang; Xushan Liu; Chunling Zhang; Yue Liu; Yihui Yuan (Microorganisms, 2020)
The emergence of multidrug-resistant bacterial pathogens has severely threatened global health. A phage with the ability to efficiently and specifically lyse bacteria is considered an alternative for controlling multidrug-resistant bacterial pathogens. The discovery of novel agents for controlling the infections caused by K. pneumoniae is urgent due to the broad multidrug-resistance of K. pneumoniae. Only a few phage isolates have been reported to infect multidrug-resistant K. pneumoniae. In this study, by using the multidrug-resistant K. pneumoniae strain as an indicator, a novel phage called vB_KleS-HSE3, which maintains high antibacterial activity and high physical stability, was isolated from hospital sewage. This phage infected one of four tested multidrug-resistant K. pneumoniae strains. This phage belongs to the Siphoviridae family and a comparative genomic analysis showed that this phage is part of a novel phage lineage among the Siphoviridae family of phages that infect strains of Klebsiella. Based on its features, the vB_KleS-HSE3 phage has potential for controlling infections caused by multidrug-resistant K. pneumoniae.